Experimental Analysis of Tire Inflation Pressure Effects on Fuel Consumption and CO₂ Emissions in a Gasoline-Powered Light Vehicle - Hakim, Moh Azizi; Maulana, Rizqi Adi; Sukmara, Sony; Heriyana, Erik; Qudratullah, Fahmi (Integrated Mechanical Engineering Journal, 2023)
Fuel consumption reduction remains an important issue in automotive engineering because it affects vehicle operating costs, energy efficiency, and carbon dioxide emissions. One of the practical factors influencing fuel consumption is tire inflation pressure. Under-inflated tires increase tire deformation and rolling resistance, which require additional engine power to maintain vehicle motion. This study aims to analyze the effect of tire inflation pressure variation on fuel consumption and estimated CO₂ emissions in a gasoline-powered light vehicle. The experimental design used four tire pressure levels, namely 26 psi, 30 psi, 33 psi, and 36 psi. Fuel consumption was measured using the full-to-full method on a fixed driving route under controlled operating conditions, including vehicle load, fuel type, route distance, and driving behavior. CO₂ emissions were estimated using a gasoline emission conversion factor. The experimental template shows that lower tire pressure tends to increase fuel consumption. At 26 psi, the vehicle recorded the highest fuel consumption, while pressure near the manufacturer’s recommendation produced lower fuel consumption. The estimated CO₂ emissions followed the same pattern because they were directly proportional to the amount of gasoline consumed. These findings indicate that tire pressure maintenance can contribute to fuel efficiency improvement and emission reduction without requiring modification of the engine system. The main contribution of this study is the formulation of a simple experimental framework for evaluating tire pressure, fuel economy, and emission relationships in light vehicles. This research is relevant for automotive maintenance practice, energy efficiency studies, and sustainable transportation engineering.